(untitled) (Journal of Parents and Teachers, 2014)
The habits of Spanish society have changed in the 21st century and one of the aspects that most concern is the leisure of youth. The forms of leisure in which alcohol is present congregate almost half of the adolescent population. One of the biggest concerns of young people is their leisure, but sometimes this is not done in the right way. This article explains the causes and consequences of the “botellón” and where we currently go, as well as ideas for achieving active and healthy leisure.